Soil organic carbon in tropical shade coffee agroforestry following land‐use changes in Mozambique - Tarquinio Mateus Magalhães; Rafael Bohn Reckziegel; João Paulino (Agrosystems, Geosciences & Environment)
Abstract Coffee (Coffea L.) agroforestry systems (CAFS) and wooded grasslands (WG) have been pointed out as having high soil organic carbon (SOC) storage potential compared to monoculture systems. Studies analyzing the response of soil bulk density (BD) and SOC to the conversion of WG to slash‐and‐burn agriculture (SBA) and to CAFS are lacking in southern Africa. This study was conducted in the buffer zone of Gorongosa National Park (Mozambique), where depth profiles of BD and SOC were estimated to 0‐ to 100‐cm soil depth in WG, SBA, and CAFS sites, with coffee shrubs aged 3, 5, and 8 years after planting. The stratification ratio (SR) was used as an indicator of soil quality and recovery from disturbance. BD and SOC stocks varied significantly among land use systems and coffee ages only in the surface soil layer (0–20 cm). SOC stocks of the surface soil and SR increased with increasing coffee age. Compared to SBA, significant increases in SOC stocks were only observed 5 years after implementation of CAFS. WG conversion to SBA did not alter SOC stocks in any soil layer; however, it led to decreased SR. Surface SOC stocks were 25.6 and 33.7 Mg ha−1 in WG and SBA, and 28.0, 41.9, and 61.1 Mg ha−1 in 3‐ and 5‐ and 8‐year‐old CAFS (mean SOC accumulation of 6.65 Mg ha−1 year−1). This study reveals that CAFS have the potential to increase belowground carbon sequestration when compared to SBA and WG over comparable soils, making it a practical option for climate change mitigation.